Performing cultural tourism : communities, tourists and creative practices / Edited by Susan Carson and Mark Pennings - Carson, Susan Edited
"While experiential staging is well documented in tourism studies, not enough has been written about the diverse types of experiences and expectations that visitors bring to the tourist space and how communities respond to, or indeed challenge, these expectations. This book brings together new ideas about cultural experiences and how communities, creative producers, and visitors can productively engage with competing interests and notions of experience and authenticity in the tourist environment. Part I considers the experiences of communities in meeting the needs of cultural tourists in an international context. Part II analyses the relationships between individualcultural tourists, the community, and digital technology. Finally, Part III responds to new methodologies in relation to interactions between government and regional policy and community development. Focusing on the way in which communities and visitors ́ 'perforḿ'; new forms of cultural tourism, Performing Cultural Tourism is aimed at undergraduate students, researchers, academics, and a diverse range of professionals at both private and government levels that are seeking to develop policies and business plans that recognize and respond to new interests in contemporary tourism."--Provided by publisher.